Retrofit pada Bangunan Komersial: Tinjauan Masalah dan Metode - Annisa Fikriyah Tasya; Purwanita Setijanti; Asri Dinapradipta (ARSITEKTURA, 2020)
At present energy efficiency is the main target to reduce building operating costs and achieve sustainability. The use of energy in buildings can be done through retrofitting. In addition, retrofitting has the potential to reduce carbon emissions, but there are also those who have to release some building features if necessary, energy features that are applied to existing buildings that have been issued to carry out renovations. Building reinforcement is a complex act, with various criteria that must be met with each other to achieve sustainable use of buildings. This article discusses the benefits, criteria, analytic methods, and decision making processes used to improve commercial buildings. The main criteria for increased energy consumption. Some other criteria are building materials, economy and occupants' needs. The analytical method for estimating or measuring the increase in retrofit that will be discussed in this article is a simulation of building energy. This method is widely used because it can predict the condition of buildings in the future. Each retrofit step is chosen and approved by the several factors; regulations, risks, business sustainability, knowledge, awareness and occupant demand. The retrofit valuation process is based on the value at which financial performance is taken into account. Retrofitting carried out on commercial buildings, applied with care, not only provides opportunities to reduce energy consumption and carbon emissions, but can also increase the value of these properties.